TRANSFORMATION OF ACCOUNTING PROFESSIONS AND OPPORTUNITIES FORMING NEW COMPETENCIES AT THE UNIVERSITY - Sorokina, V.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The last decade has been characterized by global changes in all spheres of the world order. The key trends of the modern world are primarily related to technological changes. Technological and social changes taking place in all spheres of life: economy, education, psychology, require adequate solutions to emerging risks. The article discusses the trends in the development of the profession of accountant, analyst, auditor through the prism of the requirements of employers to the competencies of future employees. The ways of interaction between companies and educational institutions for the formation of the required competencies are presented. Special attention is paid to the problems of education arising in connection with global changes and the possibilities of compliance with these changes in the educational environment. The profession of accountant, analyst, auditor is rapidly transforming under the influence of technology development. The prospects of professional practices are quite obvious: the transfer of most of the technical functions of document processing to computers, artificial intelligence will make the accountant a decision-maker based on his professional judgment on the formation of valuable information for management. This will require the next generation of practicing accountants to develop new competencies in information technology, strategic planning and communications with the business environment. The vector of these changes is already noticeable in large companies (including audit), but in the next decade these requirements will become relevant for smaller companies. Company management uses digital technologies to search, collect and process big data, which allows to increase the efficiency of planning, organization and control processes. Software platforms, artificial intelligence and neural networks are developing.